PENGARUH INTENSITAS MODAL, INTENSITAS PERSEDIAAN, KEBIJAKAN UTANG TERHADAP TAX AGGRESSIVENESS - Agfiyanti, Mustika; Agustinus, Erick (Publika Citra Media, 2025)
This study aims to provide empirical evidence of the effect of Capital Intensity, Inventory Intensity and Debt Policy on Tax Aggressiveness in Food and beverage sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. This type of research is quantitative research. The type of data used is secondary data. The research sample was taken using purposive sampling technique. The total data obtained was 80 data. Data analysis techniques using Eviews 9. The results of this study indicate that Capital Intensity, Inventory Intensity and Debt Policy simultaneously affect Tax Aggressiveness. The results of the study partially show that Capital Intensity partially affects on Tax Aggressiveness, while Inventory Intensity and Debt Policy partially have not affect on Tax Aggressiveness.